Is American manufacturing in decline? - KLIESEN, Kevin L.; John A. TATOM (Journal of Economics Bibliography, 2025)
There is a widespread popular view that American manufacturing is in decline. This declinist view reflects many factors. First, real GDP growth during the current business expansion has been the weakest in the post-WWII period. Second, over the decade from 2000 to 2010, manufacturing employment has declined by about 6 million. Third, persistent manufacturing trade deficits have led many observers to conclude U.S. competitiveness has eroded. This paper discusses these arguments and suggests a competing view that, instead, U.S. manufacturing is a leading growth sector and has remained strongly competitive internationally. On balance, we show that traditional domestic economic forces adequately explain recent trends in U.S. manufacturing output and employment growth. Finally, we argue that the recent reduction in the corporate income tax rate may further boost the fortunes of the U.S. manufacturing sector, although this favorable development could be offset by a more restrictive international trade regime. Keywords. Intra-industry trade; Imperfect competition; Classical theories of trade. JEL. F11; F12; F13.